Nutritional Interventions and Health Education in the Prevention of Chronic Energy Deficiency in Pregnant Women: Scoping Review - Putri Adila, Wiwie; Surahmi M, Sari (Rifa'Institute, 2025)
Introduction: Chronic Energy Deficiency (CED) among pregnant women is a persistent public health challenge with far-reaching implications for maternal and fetal outcomes. Nutritional interventions without concurrent health education are often inadequate. Objective: This review aims to examine the effectiveness of nutritional and health education strategies in the prevention of CED in pregnant women. Methods: Scoping review was conducted by selecting 10 peer-reviewed articles published between 2018 and 2024, identified through systematic searches in PubMed, Scopus, ScienceDirect, and Google Scholar using predetermined keywords and Boolean operators. Results and Discussion: The review found that integrated interventions—comprising nutrition education, health professional training, and supplementary feeding—significantly reduce CED prevalence. These interventions were most effective when sustained over time, incorporated family, and community engagement, and were embedded within primary healthcare systems. Conclusion: A multidimensional and context-specific approach that blends nutrition and education is vital for the effective prevention of CED in pregnant women. Strengthening policy frameworks and ensuring program sustainability are key to achieving long-term improvements in maternal health.